THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE ABOUT THE PREVENTION OF KIDNEY FUNCTION DISORDERS AND WATER CONSUMPTION IN STUDENTS MAJORING IN OFFICE AT SMK MUHAMMADIYAH 3 TANGERANG SELATAN - Suryadi, Suryadi; Wahyudin, M Didin; Hardianti, Tita (Edu Dharma Journal :Jurnal penelitian dan pengabdian masyarakat, 2025)
ABSTRACTKidney function disorders are conditions in which the kidneys cannot work properly in filtering waste and toxins from the blood in the human body, causing various diseases, namely acute kidney failure, chronic kidney failure, kidney stones and urinary tract infections. Research Objectives To determine the relationship between the level of knowledge about the prevention of kidney function disorders and water consumption in students majoring in office at SMK Muhammadiyah 3 South Tangerang. This research method is a quantitative research with a cross sectional approach to test the relationship between the level of knowledge and water consumption in students majoring in office at Smk Muhammadiyah 3 South Tangerang. The results showed that the value of the correlation coefficient R = 0.350, which indicates a weak positive relationship between the two variables studied. This means that when one variable increases, the other tends to increase, but this relationship is not very strong. In addition, a significance value of P=0.000 ≤ 0.05 indicates that this relationship is statistically significant at a 95% confidence level. In other words, it is unlikely that this relationship occurred by chance, so it can be said that the relationship between the two variables does exist and has a strong statistical basis. Conclusion of the relationship between the level of knowledge about the prevention of kidney dysfunction and water consumption in adolescents majoring in office at SMK Muhammadiyah 3 South Tangerang with a P-value of 0.000 ≤ 0.005. Suggestion It is hoped that this research can be an additional reference for STIKes Wdya Dharma Husada students, especially in the field of nursing, regarding the prevention of kidney function disorders against water consumption. This information can be used as material for further studies related to the prevention of kidney dysfunction in adolescents.                                                   ABSTRAKABSTRAK Gangguan fungsi ginjal adalah kondisi ginjal tidak dapat berkerja dengan baik dalam menyaring limbah dan racun dari darah pada tubuh manusia sehingga menyebabkan berbagai penyakit yaitu gagal ginjal akut, gagal ginjal kronis, batu ginjal dan infeksi saluran kemih. Tujuan Penelitian Mengetahui hubungan tingkat pengetahuan pencegahan gangguan fungsi ginjal terhadap konsumsi air putih pada siswa jurusan perkantoran di SMK Muhammadiyah 3 Tangerang Selatan. Metode penelitian ini merupakan penelitian kuantitatif dengan pendekatan cross sectional Untuk menguji hubungan antara tingkat pengetahuan dan konsumsi air putih pada siswa jurusan perkantoran di Smk Muhammadiyah 3 Tangerang Selatan. Hasil penelitian menunjukkan bahwa nilai koefisien korelasi R= 0,350, yang mengindikasikan adanya hubungan positif lemah antara kedua variabel yang diteliti. Artinya, ketika satu variabel meningkat, variabel lainnya cenderung ikut meningkat, namun hubungan ini tidak terlalu kuat. Selain itu, nilai signifikansi P=0,000 ≤ 0,05 menunjukkan bahwa hubungan ini secara statistik signifikan pada tingkat kepercayaan 95%. Dengan kata lain, kecil kemungkinan bahwa hubungan ini terjadi secara kebetulan, sehingga dapat dikatakan bahwa hubungan antara kedua variabel memang ada dan memiliki dasar statistik yang kuat. Kesimpulan hubungan tingkat pengetahuan pencegahan gangguan fungsi ginjal terhadap konsumsi air putih pada remaja jurusan perkantoran di SMK Muhammadiyah 3 Tangerang Selatan dengan nilai P-value 0,000 ≤ 0,005. Saran Diharapkan penelitian ini dapat menjadi referensi tambahan bagi mahasiswa STIKes Wdya Dharma Husada, khususnya di bidang keperawatan, mengenai pencegahan gangguan fungsi ginjal terhadap konsumsi air putih. Informasi ini dapat sebagai bahan kajian lebih lanjut terkait pencegahan gangguan fungsi ginjal pada remaja.